Influence of compost covers on the efficiency of biowaste composting process - Marešová, Karolina; Kollárová, Mária (Waste management (New York, N.Y.), 2010)
The temperature of matured compost is an indicator of feedstock quality and also a good feedback informing about the suitability of an applied technological procedure. Two independent experiments using the technology of windrow composting at open area were conducted with the final goal to evaluate the effect of compost pile covering (in comparison with uncovered piles) on the course of composting process - behaviour of temperature over time and oxygen content. Two types of sheets were used - Top Tex permeable sheet and impermeable polyethylene sheet. The experiment I (summer months) aimed at comparison of efficiency between the Top Tex sheet cover and the uncovered compost piles, while experiment II (autumn months) compared treatments using the Top Tex sheet and polyethylene sheet by contrast. Within the experiment I the composts consisted of cattle slurry and fresh grass matter at a ratio of 1:1, in case of experiment II consisted of pig/cattle manure, fresh grass matter and chipped material at a ratio of about 1:2:1. The obtained data showed no significant differences among the cover treatments according to ANOVA. The only exception was oxygen content in pile 4 (experiment II) under Top Tex sheet, where a markedly higher oxygen content than under polyethylene sheet was measured during the whole composting period. It was the only case where statistical analysis proved a significant difference; the p-value was 0.0002.
Keywords: měření biologické spotřeby kyslíku; Waste Products; Biological Oxygen Demand Analysis; nakládání s odpady; Soil; Temperature; Polyethylene; odpadní produkty; polyethylen; Waste Management; půda; teplota